2005
DOI: 10.1080/02770900500265157
|View full text |Cite
|
Sign up to set email alerts
|

Learning Preferences of Caregivers of Asthmatic Children

Abstract: The majority of caregivers preferred the kinesthetic learning method, whether as a single learning preference or in combination with other approaches. Incorporating kinesthetic methods of learning, such as role plays and problem-solving case scenarios, into standardized asthma education curricula may be beneficial to patients and families in terms of understanding and using their regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
1
10
0
4
Order By: Relevance
“…These findings are compatible with other studies (9,14,16) that have used the VARK questionnaire as a learning style inventory. These findings are compatible with other studies (9,14,16) that have used the VARK questionnaire as a learning style inventory.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are compatible with other studies (9,14,16) that have used the VARK questionnaire as a learning style inventory. These findings are compatible with other studies (9,14,16) that have used the VARK questionnaire as a learning style inventory.…”
Section: Discussionsupporting
confidence: 93%
“…The education, psychology, and cognitive learning literature widely reflects the use of many different learning style assessments to evaluate individual preferences (Desmedt & Valcke, 2004;James & Blank, 1993) and how they can be used for personalized instruction. Although used extensively in general educational and biomedical research to measure student learning preferences, tools designed to assess learning styles have received little attention in clinical settings to inform health communication (Carbone, Lennon, Torres, & Rosal, 2005;Dinakar, Adams, Brimer, & Silva, 2005). Several investigators describe the need to assess learning styles for patient education, yet few implemented interventions that adapt material to specific learning modality preferences (Beagley, 2011;Cavanagh & Coffin, 2004;Inott & Kennedy, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Patients often exhibit distinctive learning styles that may be restricted to visual, aural, reading/writing, kinesthetic styles, or a multimodal combination of these patterns. 33 As such, each patient possesses a unique learning fingerprint that is most likely to be accessed through multiple and often diverse mechanisms. A unique aspect of our intervention involved kinesthetic teaching, which gives the patient an opportunity to gain "handson" experience that builds confidence, an important motivator in performing health protective behavior.…”
Section: Commentmentioning
confidence: 99%
“…This has been used successfully for patients with diabetes mellitus who must perform precise health protective behaviors to control their disease. 33,34 Glazebrook et al 19 studied the efficacy of Skinsafe software to educate high-risk patients in a primary care setting and found that those who participated in the intervention were 1.67 times more likely to perform SSEs or "mole checks" after the intervention. In our study, those in the intervention group were 2.36 times more likely to perform SSEs after the intervention.…”
Section: Commentmentioning
confidence: 99%